2015
DOI: 10.1128/mbio.01660-15
|View full text |Cite
|
Sign up to set email alerts
|

Joint Transcriptional Control of Virulence and Resistance to Antibiotic and Environmental Stress in Acinetobacter baumannii

Abstract: The increasing emergence of antibiotic-resistant bacterial pathogens represents a serious risk to human health and the entire health care system. Many currently circulating strains of Acinetobacter baumannii exhibit resistance to multiple antibiotics. A key limitation in combating A. baumannii is that our understanding of the molecular mechanisms underlying the pathogenesis of A. baumannii is lacking. To identify potential virulence determinants of a contemporary multidrug-resistant isolate of A. baumannii, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 61 publications
6
125
2
1
Order By: Relevance
“…For example, Peleg et al found that A. baumannii was more lethal in the Galleria model than non-baumannii Acinetobacter species, including A. baylyi and A. lwoffii, and that antibiotic therapy improved survival of the infected larvae (75). Gebhardt et al also found that A. baumannii, even a strain considered to be avirulent (ATCC 17978), was more virulent than A. baylyi, in Galleria (76). Wand et al reported that strain to strain differences in biofilm formation did not correlate with virulence (77).…”
Section: Models Of Infectionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Peleg et al found that A. baumannii was more lethal in the Galleria model than non-baumannii Acinetobacter species, including A. baylyi and A. lwoffii, and that antibiotic therapy improved survival of the infected larvae (75). Gebhardt et al also found that A. baumannii, even a strain considered to be avirulent (ATCC 17978), was more virulent than A. baylyi, in Galleria (76). Wand et al reported that strain to strain differences in biofilm formation did not correlate with virulence (77).…”
Section: Models Of Infectionmentioning
confidence: 98%
“…For example, A. baumannii grew better at 37°C and was better able to resist macrophage uptake than these other species in one study (86). As mentioned, A. baumannii strains were also more lethal to the wax moth larva of Galleria than strains of A. baylyi and A. lwoffii (75,76). In another study, a strain of A. junii was nonlethal in neutropenic mice, whereas several A. baumannii strains were lethal (85).…”
Section: Acinetobacter Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenicity involves several virulence factors in combination with with metabolic capabilities and resistance to environmental stresses. Adaptation to stress involves intricate and interconnected regulatory pathways that integrate environmental signals with growth and survival decisions that in turn impact pathogenic potential [8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports of the genetic requirements for A. baumannii persistence identify virulence factors as zinc and iron acquisition systems, capsule and LPS biosynthesis genes, amino acid metabolism and acquisition genes, and the bfmRS TCS but more studies are needed to increase knowledge in these aspects [10].…”
Section: Survival Of a Baumannii Under Stress Conditionsmentioning
confidence: 99%